PERSEPSI PENUMPANG TERHADAP LAYANAN MRT DI STASIUN BLOK M - Najla Dara Ayunda; Anggrelita Mutiara Salsabila Dewi; Gabriella Dofani Natalia Siregar; Achmad Aidil Viqri; Ridwan; Faris Widiyatmoko (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze passenger perceptions of service quality at MRT Blok M Station in Jakarta, as well as to identify factors contributing to satisfaction and dissatisfaction. A qualitative descriptive approach was employed, with data collected through an online survey using Google Form consisting of open-ended essay questions distributed to 32 respondents selected via purposive sampling. Data were analyzed through qualitative content analysis using Braun and Clarke's thematic analysis model and interpreted within the SERVQUAL framework. The results show that passenger perceptions are generally positive across six dimensions: physical access and inclusivity (87.5%), navigation and information systems (96.9%), staff service quality (65.6%), operational punctuality (46.9%), station facility conditions (87.5%), and safety and comfort (84.4%). However, several issues require attention, including misuse of disability facilities, limited escalator coverage, inefficient tap-in/tap-out placement, and overcrowding during peak hours. These findings provide empirical input for MRT Jakarta's ongoing service improvement efforts.